Διερεύνηση συστημάτων ιχνηλασιμότητας σε βιομηχανίες πουλερικών - Νεοκλέους, Ιωάννα (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This project deals with the traceability systems which apply in food industries and describes how important its implementation is. It focuses in poultry production chains and underlines the importance of applying the traceability system in food industries. Particularly, in the first part general clues about traceability are mentioned and why the system is important. Additionally, the risks and human diseases that can be caused by consuming poultry products are listed. In the second part, an overview of the globally and applicable traceability systems are given while the present, future and application failures with prospects are discussed. In the third part, the traceability procedure of a major, local poultry meat producer is described. The description focuses from cutting to the market. The fourth part, deals with problems in managing the underlying traceability system and recommendations for improvement are given, taking into account what has been investigated in the first and second part of the dissertation.
Keywords: Traceability; Poultry production system; Safety; Quality; Ιχνηλασιμότητα; Συστήματα ιχνηλασιμότητας στα κοτόπουλα; Ασφάλεια; Ποιότητα